ANALYSIS OF REJECTION OF APPLICATION FOR MARRIAGE ISBAT AND ORIGIN OF CHILDREN - Nurhalimah Nurhalimah (Sean Institute, 2021)
Isbat marriage is a process of ratifying the marriage of a married couple who previously had a sirri marriage. The purpose of marriage isbat is to obtain a marriage certificate as proof of the validity of the marriage in accordance with the legislation in force in Indonesia. As stipulated in Law No. 1 of 1974 concerning Marriage, article 2 paragraph (2) and the implementation of marriage isbat is only intended for certain matters as in Article 7 paragraph (1), (2), (3) KHI. In the determination of the Blora Religious Court, it was found that there was a determination of the application for isbat marriage for sirri marriages which was accumulated with the determination of the origin of the child register Number: 0056/Pdt.P/2015/Pa.Bla. Panel of Judges at the Blora Religious Court. did not grant all requests. In the determination, a husband and wife want to ratify their sirri marriage and determine the child from the marriage as their legal child. number: 0056/Pdt.P/2015/PA.Bla?. What are the legal consequences for the determination of the case related to the protection of children's civil rights? This type of research is juridical-empirical research. The primary data used is the case file of the Blora Religious Court Number: 0056/Pdt.P/2015/Pa.Bla. and an interview with the Judge who decided the case Number: 0056/Pdt.P/2015/PA.Bla. Data collection techniques are interviews and documentation. while the analysis technique uses descriptive-analysis. The results showed that 1). the determination of the Blora Religious Court Number: 0056/Pdt.P/2015/PA.Bla in the case of the application for marriage isbat and the origin of the child is still not able to provide justice and benefits for the justice-seeking community. That is not being able to provide protection, especially to the child, even though the child was born as a result of a legal sirri marriage, it's just that according to state law the conditions and pillars are not fulfilled, because the woman is